2008
DOI: 10.1213/01.ane.0000287665.96156.72
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Detailed, Video-Assisted Anesthesia Risk Education on Patient Anxiety and the Duration of the Preanesthetic Interview: A Randomized Controlled Trial

Abstract: Our study suggests that the use of a video for detailed anesthesia risk education does not change patient anxiety, but leads to a better understanding of the procedure and risks of anesthesia. When the video is shown before the preanesthetic interview, the interview is longer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
2
6

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(78 citation statements)
references
References 28 publications
5
58
2
6
Order By: Relevance
“…Previous research has identified the significance of anxiety and fear during the pre-anesthetic interview [17][18][19][20]. Whilst Salzwedel et al demonstrated no improvement of patient's baseline anxiety after the pre-anesthetic interview; Bondy et al found a statistically significant improvement in patient's anxiety with the use of multimedia patient information [19].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has identified the significance of anxiety and fear during the pre-anesthetic interview [17][18][19][20]. Whilst Salzwedel et al demonstrated no improvement of patient's baseline anxiety after the pre-anesthetic interview; Bondy et al found a statistically significant improvement in patient's anxiety with the use of multimedia patient information [19].…”
Section: Discussionmentioning
confidence: 99%
“…41 In particular, video information would provide the patient with a better understanding of the medical intervention. 42,43 These methods could be implemented within, for example, a multimodal prehabilitation program that has physical, nutritional, and psychological aspects. The prehabilitation programs could enhance postoperative recovery using preoperative interventions tailored to the population of interest.…”
Section: Future Considerationsmentioning
confidence: 99%
“…While referring to the patient, instead of first-or third-person singular, second-person singular should be used; active sentences should be used instead of passive sentences, and instead of medical terms, short and common words from spoken language should be used (23)(24)(25).…”
Section: How Should We Increase the Rate Of Reading Icd?mentioning
confidence: 99%
“…It has been documented that, in addition to simple drawings and shapes, giving images of surgical intervention and anaesthesia processes via informative leaflets or multimedia means like CD and DVD to the patients does not increase the uneasiness of the patients and actually contributes to the operation being better understood (25,26).…”
Section: How Should We Increase the Rate Of Reading Icd?mentioning
confidence: 99%